Prevalence of posttraumatic stress disorder and associated factors among displaced people in Africa: a systematic review and meta-analysis - Andualem, Fantahun; Melkam, Mamaru; Takelle, Girmaw Medfu; Nakie, Girum; Tinsae, Techilo; Fentahun, Setegn; Rtbey, Gidey; Begashaw, Tesfaye Derbie; Seid, Jemal; Tegegn, Lidiya Fasil; Gedef, Getachew Muluye; Bitew, Desalegn Anmut; et al. (Frontiers in Psychiatry, 2024)
Background: Globally, theThe number of individuals people who have been displaced from their homelandhomes due to war, conflict or violence, or conflict, and natural disasters Displaced. The reviews stated that the pooled prevalence of PTSD among refugees in high-income countries was higher than the general population. The However, there has been no review done on PTSD among displaced persons in Africa. Therefore, the aim of this systematic review and metaanalysis iswas to summarise the most recent availabledata evidence on the pooled prevalence of posttraumatic stress disorder and its pooled effect of associated factors of the adult displaced people in Africa.We used an appropriate guideline for systematic reviews and meta-analyses reports, which is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This review protocol was registered in PROSPERO (CRD42023411371). The publications were identified from PubMed/Medline, EMBASE, the Cochrane Library, Scopus databases, and other grey searches. The included papers were the original data that reported the prevalence of PTSD and/or associated factors among displaced people (>=18 years old), published in English, and papers available online from January 1, 2000, to April 30, 2023. of Google Scholar, and World Health Organization (WHO) reports. The data was extracted in Microsoft Excel, and then it will be imported into STATA 11.0 for analysis. 4Results: We have included 10 studies conducted in African countries with 5287 study participants.In this meta-analysis, the pooled prevalence of PTSD among displaced people in Africa was 55.64 (95% CI: 42.76-68.41%). Further, in subgroup analysis regarding the study participants, the pooled prevalence of PTSD among internally displaced people and refugees was 56.35% and 54.04%, respectively. Among associated factors, being female, single, and unemployed, as well as substance use disorder and depression, were significantly related to PTSD among displaced people.In this review, the pooled prevalence of PTSD among displaced people in Africa was high.DemographicThe demographic characteristics (female, single, and unemployed), substance use disorder, and depression were risk factors for PTSD among displaced people.